Effectiveness of collaboration technology in Polyclad laminates Kuching Sdn. Bhd. - Fong,, Tze How. (2003)
The paper main purpose is to conduct research on the development of successful enterprise collaboration model, with the use of various collaboration technologies. The research also takes an insight look at the people involvement in the collaboration process, the human behavior and the relationship of worker in the collaboration process, and lastly, their contribution to the building of the collaboration system.